2-connected graphs with the minimum algebraic connectivity. Issue 21 (20th December 2022) - Yu, Guanglong; Sun, Lin; Zhang, Hailiang; Wu, Yarong
Abstract : Among all simple 2-connected graphs, and among all θ -graphs, the graphs with the minimum algebraic connectivity are completely determined, respectively.